HMI sebagai Organisasi Perkaderan dalam Mewujudkan Pemimpin Good Governance - Abd. Rahman (STAI DDI Kota Makassar, 2021)
Leadership with regard to someone influencing other people’s behavior for a purpose With power, a leader can influence the behavior of others for a purpose. Power can be divided into five, namely: (1) power expertise (expert power); (2) legitimate power (legitimate power); (3) reference power (referent power); (4) reward power; (5) coercive power. Basically, it becomes an absolute that humans were created by Allah SWT on the surface of the earth to devote themselves solely to their presence as stated in the Koran that humans were created as “khalifa fil ard” (leaders on earth). In the course of human history in the field of leadership, many phenomena have occurred in the dynamics of this journey. Where than the existence of ideal leadership is very coveted in every society. It becomes a logical consequence of how the ideal leadership and a good and responsible leader can be realized. So it is very much needed the candradimuka creater (appropriately galvanizing) a leader who is critical and can answer the challenges of changing times by him the Islamic Student Association (HMI) is here to then become an answer as a complete cadre organization from formal and informal cadre levels.